A dynamic inventory rationing policy for business-to-consumer e-tail stores in a supply disruption context. (April 2020) - Jimenez G, Hanser S.; Rodrigues, Tulio F.O.; Dantas, Misia M.; Cavalcante, Cristiano A.V.
Highlights: An order planning policy based on inventory rationing is developed. The model considers constraints of unexpected supply disruptions. A comprehensive numerical experiment on order planning is conducted. The proposed policy diminishes the consequences of the supply disruptions. The new policy is profitable, service-oriented, low penalty-cost and it is made of intuitive rules. Abstract: A core activity for achieving an efficient order fulfillment planning in the business-to-consumer (B2C) context is the inventory rationing. This activity is complex and vital once e-tailers must deal with high frequency orders, timely delivery needs, and frequent stock outs, having to employ other fulfillment alternatives such as dropshipping. Particularly, it becomes much more complex when supply disruptions occur. When some eventualities like the malfunctioning of the warehouse management system, a road blockage or a disaster occurs in an unexpected way e-tailers or supplier inventory can result damaged and the access to some geographic areas can be compromised, making hard to manage the inventory. As a consequence, some clients are hampered of receiving their products at the expected time, quantity or quality. This paper puts forward a framework for order fulfillment planning in e-tail stores, based on an inventory rationing model that splits the demand in a partial drop-shipping system. The model does consider the effects of supply disruption, filling the gap of existing models that do not include the respective constraints. Moreover, it reserves the more profitable and lesser inventory-consuming orders for the e-tailer, enabling him to diminish the consequences of the supply disruptions and achieve a profitable and service-oriented fulfillment operation.